A Review of Producer Adoption in the U.S. Beef Industry with Application to Enteric Methane Emission Mitigation Strategies - Jaime R. Luke; Glynn T. Tonsor (Animals)
Cattle are ruminant animals that produce enteric methane (CH4) emissions as a byproduct of their natural digestive process. U.S. beef producers have been receiving pressure to reduce production emissions. The scientific community continues to research and develop methods to reduce enteric methane emissions, but adoption of such strategies by U.S. beef producers remains unknown. We complete a review on producer adoption in the U.S. beef industry to shed light on potential factors that may impact the adoption of emissions-mitigating strategies by U.S. beef producers. After querying nine research databases, fifty-five studies were gathered and synthesized. These studies span the beef supply chain and focus on topics including feed additives, management practices, and reproductive technologies. Economic returns are a key driver of U.S. beef producer adoption decisions, with accompanying considerations for the impacts on consumer perceptions and demand. Segmentation in the U.S. beef supply chain, with animals typically changing ownership multiple times prior to slaughter, may result in challenges in tracing and verifying the adoption of climate-focused strategies. Targeting large-scale producers may be the most efficient avenue to achieving emissions reduction goals via the adoption of methane-mitigating strategies. Younger producers could additionally be a target demographic for adoption efforts.